The Development of Information management System according to the Personal Data Protection act for Rajabhat University - Khamsom, Chakkrit; Arreerard, Tharach; Lagdee, Apichat (Journal for Developing the Social and Community, 2024)
This research aims to: 1) Synthesize the components of the information management system according to the Personal Data Protection Act For Rajabhat University, 2) Develop an information management system in accordance with the Personal Data Protection Act For Rajabhat University and 3) Study the results of the trial of using the information management system according to the Personal Data Protection Act. For Rajabhat University. The target group includes Group 1, 9 experts evaluating suitability, Group 2, Maha Sarakham Rajabhat University personnel, 17 departments, 2 people each, totaling 37 people. The tools used in 1) a questionnaire on suitability of components, 2) a questionnaire on suitability of the system, 3) a questionnaire on satisfaction with the manual, 4) a questionnaire on perception of the manual, 5) a questionnaire on satisfaction with the system, and 6) System Perception Questionnaire. The statistics used are as follows: average and standard deviation. The results of this research were as follows: 1) Components of the information management system according to the Personal Data Protection Act (1) system architecture (2) system modules and (3) system user composition Expert opinion Overall, it is appropriate at the highest level. 2) Information management system according to the Personal Data Protection Act For Rajabhat University, it is divided into 3 parts: (1) the login section, (2) the data management system login, and (3) the report management system login, expert opinions. Overall, it is suitable at the highest level. 3) The results of the system trial found that opinions on the system user manual Overall, it is at a high level. Opinions about the system Overall it is at a high level. Opinions on awareness/understanding of the Personal Data Protection Act Overall it is at a high level. Comments on perception/understanding of the manual Overall it is at a high level. and opinions on perception/understanding of the system Overall it is at a high level.